Methotrexate Versus Methotrexate Plus Folic Acid in the Treatment of Moderate to Severe Plaque Psoriasis: A Randomized Clinical-Trial - D.K. Khadka; S. Agrawal; T.K. Dhali (Nepal Journal of Dermatology, Venereology & Leprology)
Background: Psoriasis is a chronic, recurring inflammatory disease affecting the skin, joints and nails that has a significant negative impact on the quality of life. Efficacy of methotrexate versus combination of methotrexate plus folic acid in the treatment of psoriasis has been rarely assessed.